The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1021/ac802491y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Liquid-Junction/Low-Flow Interface for Phosphate Buffer Capillary Electrophoresis Mass Spectrometry

Abstract: To alleviate ion suppression from phosphate buffer and to preserve separation integrity, a new capillary electrophoresis mass spectrometry (CE-MS) interface was developed. The interface consisted of a low-flow interface and a liquid junction. In this design, both the inlet reservoir and the liquid-junction reservoir were filled with phosphate running buffer. Because the phosphate anions in the column migrated toward the inlet reservoir (away from the electrospray ionization (ESI) source) the problem of ion sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…(A)) consisted of a poly(methyl methacrylate)‐based liquid reservoir and a tapered tip as the ESI sprayer. A 1.5 cm × 700 μm id × 850 μm od fused‐silica capillary was tapered to produce a 5 μm orifice according to the procedure reported previously . The fused silica was drawn manually using a vertically suspended section of capillary to which a small weight (45 g) had been attached.…”
Section: Methodsmentioning
confidence: 99%
“…(A)) consisted of a poly(methyl methacrylate)‐based liquid reservoir and a tapered tip as the ESI sprayer. A 1.5 cm × 700 μm id × 850 μm od fused‐silica capillary was tapered to produce a 5 μm orifice according to the procedure reported previously . The fused silica was drawn manually using a vertically suspended section of capillary to which a small weight (45 g) had been attached.…”
Section: Methodsmentioning
confidence: 99%
“…In CE, to reduce ion suppression due to the use of phosphate ions, a L–J interface was also used being phosphate anions moving in the direction of the inlet capillary. When using additives such as sodium dodecyl sulphate, good results were obtained allowing the micelles to be eliminated into the liquid‐junction .…”
Section: Hephenation With Mass Spectrometrymentioning
confidence: 99%
“…Notably, it could also be concluded that the new interface could run with nonvolatile PBS directly, which is a traditional biological buffer widely used in biochemistry studies, without any additives such as methanol and acetic acid. [31][32][33] This might expand the applicable range of buffers for the current CE-MS interface.…”
Section: Ce Separation With the Ce-iesi-ms Interfacementioning
confidence: 99%